Cardiomyocyte apoptosis vs autophagy with prolonged doxorubicin treatment: comparison with osteosarcoma cells. (11th September 2014) - Tacar, Oktay; Indumathy, Sivanjah; Tan, Mei Lin; Baindur‐Hudson, Swati; Friedhuber, Anna M.; Dass, Crispin R.
Abstract Objective Doxorubicin (Dox) is a frontline chemotherapeutic against osteosarcoma (OS) that is plagued by side effects, particularly in the heart. The specific objective of this article is to investigate whether low‐dose Dox treatment had pro‐autophagic effects in cardiomyocytes as well as osteosarcoma cells. Methods This study characterises apoptotic (Bax) and autophagic (Beclin‐1) biomarker levels in human OS and cardiomyocyte cell lines as well as in various tissues when mice are exposed to low (1 mg/kg, thrice weekly) and high (3 mg/kg thrice weekly) dose Dox for a month. Key findings There was a decrease in Bax and increase in Beclin‐1 in cardiac tissue in the high‐dose group. Dox decreased Beclin‐1 in the skin and liver, with no clear indication in the stomach, small intestine and testis. At low Dox doses of 10 and 100 nm in cardiomyocytes and OS cells, there is a pro‐apoptotic effect, with a quicker response in the 100‐nm condition, and a slower but steady increase of a pro‐apoptotic response at the lower 10‐nm dose. However, electron microscopy images revealed changes to human OS cells that resembled autophagy. Human prostate, breast and colorectal cells treated with 10‐nm Dox showed ∼ 40% reduction in cell viability after 24 h. Conclusion In culture, cells of both cardiomyocytes and OS revealed a predominant pro‐apoptotic response at the expense of autophagy, although both seemed to be occurring in vivo.